Türk vergi hukukunda zamanaşımı - Turna, Fatma (My University, 2014)
Vergi hukukunda zamanaşımı, verginin tarh, tahakkuk ve tahsil aşamalarında titizlikle nazara alınması gereken önemli bir müessesedir. Bu sadece vergi güvenliği için değil, aynı zamanda vergicilikte adil olma prensibinin bir gereği olarak, mükellef hukuku bakımından düşünülmesi ve objektif olarak uygulanması gereken bir husustur. Bugün ekonominin karmaşık bir yapıya sahip olması, yeni vergilerin getirilmesi, siyasi etkiler, vergisel işlemlerin uluslararası boyutu gibi nedenlerden dolayı vergi sistemimiz oldukça karmaşık bir yapıya bürünmüş ve uygulamada bir takım sorunları karşımıza çıkartmıştır. Bu nedenle çalışmamızda, öncelikli olarak zamanaşımı konusunda teorik bilgilere yer verilmiş ve zamanaşımına ilişkin vergi uygulamalarındaki sorunlar, yargı kararları ve Maliye Bakanlığı görüşleri çerçevesinde incelenmeye çalışılmıştır. Söz konusu sorunlara yönelik öğretide yer verilen öneriler incelenerek yorumlarımız doğrultusunda değerlendirilmiştir.

THE PRESCRIPTION IN TURKISH TAX LAW Prescription in the tax law is a remarkable institution which must always be considered at the imposition, assessment and collection stages of taxing. The reason for this is not only tax security, but it's also an important consideration that must be taken with regard to taxpayer, due to the fairness principle of taxation. It must also be applied objectively. Recently, our tax system began to have a very complex structure, thanks to the complex structure of the economy, the imposition of nex taxes, political effects, and the international dimensions of tax transactions. This led to some problems of tax applications. Because of this, the theoretical knowledge on prescription is adressed primarily in this dissertation, and the problems of prescription on tax applications are examined by using judicial decisions and opinions of Ministry of Finance. The suggestions which are given as a solution to these problems are examined and evaluated in the light of our comments.
Keywords: Law and legislation; Taxation; Turkey; Türkiye; Vegilendirme; Vergi hukuku